The combination of left ventricular ejection fraction and end-diastolic diameter and outcomes in peritoneal dialysis patients: a multicenter retrospective study - Jiayin You; Ning Su; Xiaoran Feng; Fenfen Peng; Qingdong Xu; Xiaojiang Zhan; Yueqiang Wen; Xiaoyang Wang; Na Tian; Xianfeng Wu; Niansong Wang (Renal Failure)
End-stage renal disease (ESRD) is often complicated by left ventricular dysfunction, which is associated with a poor prognosis. This study aims to investigate the association between baseline left ventricular ejection fraction (LVEF) plus left ventricular end-diastolic diameter (LVEDD) with outcomes in peritoneal dialysis (PD) patients. In this multicenter retrospective study, 1,511 incident Chinese patients on PD between 1 January 2005 and 31 December 2021 were enrolled. Restricted cubic splines (RCS) were used to explore the non-linear associations between LVEF+LVEDD and the risk of mortality. Parametric models for interval-censored survival-time data (stintreg) were used to examine the association between LVEF+LVEDD quartiles and the outcomes. During 6,451.11 person-years of follow-up [median 4.81 (IQR 3.61–6.81) years], 247 (17.8%) patients died, including 88 cardiovascular deaths. RCS showed a U-shaped association between LVEF+LVEDD and the risks of all-cause and CV mortality. According to the quartiles, the optimal range of LVEF+LVEDD associated with the lowest risk of all-cause and CV mortality was 103–107, which was set as the reference range. Both higher (≥115) and lower (<103) levels of LVEF+LVEDD were associated with increased risks of all-cause mortality (hazard ratio [HR] 2.20, 95% confidence interval [CI] 1.58–3.07; HR 1.68, 95% CI 1.19–2.36) and cardiovascular mortality (HR 2.51, 95% CI 1.33–4.75; HR 1.86, 95% CI 0.96–3.61). Low and high levels of baseline LVEF+LVEDD were associated with increased risks of all-cause and cardiovascular mortality in PD patients.